Necklace-shaped dimethylsiloxane polymers bearing polyhedral oligomeric silsesquioxane cages with alternating length chains. (3rd October 2017) - Katsuta, Naohiro; Yoshimatsu, Marie; Komori, Kunihiro; Natsuaki, Tsubasa; Suwa, Kazuya; Sakai, Kiyoshi; Matsuo, Takashi; Ohba, Tomoyuki; Uemura, Shinobu; Watanabe, Satoshi; Kunitake, Masashi
Abstract: Necklace-shaped dimethylsiloxane (DMS) polymers bearing polyhedral oligomeric silsesquioxane (POSS) cages with "alternating modulated chain" arrangements were synthesized, by the polycondensation of a dimeric POSS precursor and dimethyl oligo-siloxane dichloride. Films of POSS-DMS polymers with "alternating modulated chain" arrangements were highly transparent. This observation is consistent with amorphous structures. Along with "constant chain" and "random chain" type polymers, three different chain arrangements of necklace-shaped polymers can now be produced. The physical properties of the three polymer types with constant POSS cage contents were compared. "Alternating modulated chain" type polymers had lower glass transition temperatures than the other two polymer types. This was attributed to the cooperative relaxation of long chain moieties that comprised half of the connecting chains. "Alternating modulated chain" type POSS-DMS polymers with average chain lengths of three to four exhibited heat resistances of over 470 °C in air. Graphical abstract: Highlights: Necklace-shaped dimethylsiloxane (DMS) polymers bearing polyhedral oligomeric silsesquioxane (POSS) cages. Stepwise synthesis of "alternating modulated chain" type polymers. Transparent amorphous inorganic thermoplastics with controllable Tg. High heat resistances of over 470 °C in air.